Family and School in their Shared Responsibility for Values Education - Iwona Szewczak (Rozprawy Społeczne)
Abstract Values education is understood as shaping an axiological orientation, and it appears to be a particularly difficult task in today's pluralistic society – yet it is not impossible. The task may be facilitated when the family and the school are aware of their share in responsibility for the education, and when this awareness leads to their rational cooperation. Of significance is also that the particular protagonists in the system of shared educational influence carry out their duties responsibly. The family realizes its educational share through educating for religious, philosophical and moral values, while the school educates for basic values.